The experience of conscious reflection within a general theory of learning - Dyngeland, Espen Hoff (Frontiers in Psychology, 2025)
One of the most important constructs in educational research and practice is learning. Yet, it is also one of its most complicated, ambiguous, and debated constructs. Questions regarding what constitutes the process of learning and how best to facilitate it have been addressed from numerous perspectives, often yielding competing interpretations and approaches. One aspect that is often the subject of these debates is the extent to which learning is an actively conscious activity. This study will contribute with a conceptual dialogue between different strands of scholarship that attend to the role of consciousness and the experience of learning, as well as those cognitive processes theorized to underlie these experiences. The upshot of this dialogue will be to connect the different theoretical perspectives, resulting in a wider viable conceptual apparatus to describe the experience of learning, founded in theoretical perspectives that seek to illuminate the cognitive processes that underlie these experiences.